2011
DOI: 10.1186/1475-2840-10-107
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the frequency of CD34+ bone marrow derived circulating progenitor cells and the number of diseased coronary arteries in patients with myocardial ischemia and diabetes

Abstract: BackgroundBone marrow-derived circulating progenitor cells (BM-CPCs) in patients with coronary heart disease are impaired with respect to number and mobilization. However, it is unknown whether the mobilization of BM-CPCs depends on the number of diseased coronary arteries. Therefore, in our study, we analysed the correlation between the diseased coronary arteries and the frequency of CD34/45+ BM-CPCs in peripheral blood (PB) in patients with ischemic heart disease (IHD).MethodsThe frequency of CD34/45+ BM-CPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…First, we have identified a mixed population of hematopoietic/myeloid and nonhematopoietic/endothelial ALDH hi progenitor cells from human UCB as a readily available and clinically applicable cell population with potent proangiogenic function. Second, the potential use of allogeneic UCB cells will open new avenues toward clinical cell-based therapies for ischemic disease, as mounting evidence indicates the potential for progenitor deletion and dysfunction of autologous BM cells in patients with severe diabetes and cardiovascular disease [2,[18][19][20]. Third, we have shown that neither high-level nor permanent engraftment of human cells were necessary to mediate augmentation of perfusion and improved vessel density in vivo.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…First, we have identified a mixed population of hematopoietic/myeloid and nonhematopoietic/endothelial ALDH hi progenitor cells from human UCB as a readily available and clinically applicable cell population with potent proangiogenic function. Second, the potential use of allogeneic UCB cells will open new avenues toward clinical cell-based therapies for ischemic disease, as mounting evidence indicates the potential for progenitor deletion and dysfunction of autologous BM cells in patients with severe diabetes and cardiovascular disease [2,[18][19][20]. Third, we have shown that neither high-level nor permanent engraftment of human cells were necessary to mediate augmentation of perfusion and improved vessel density in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…Despite advances in pharmacological and surgical management, ischemic disease remains one of the leading causes of morbidity and mortality worldwide [1,2]. Thus, novel therapies to promote the regeneration of damaged vasculature are under intense preclinical investigation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to documented progenitor cell dysfunction in patients with diabetes and vascular comorbidities , use of autologous progenitors to stimulate islet regeneration is predicted to show reduced efficacy . Fortunately, recent government initiatives to HLA‐phenotype and cryopreserve umbilical cord blood (UCB) samples for clinical applications has established a readily available source of allogeneic cells early in ontogeny and untouched by disease‐related pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic disease is characterized by the reduction of blood flow to the heart or peripheral tissues and encompasses life‐threatening disorders such as ischemic heart disease and critical limb ischemia. Despite advances in the management of these conditions, ischemic disease remains a leading causes of morbidity and mortality worldwide (Dotsenko, ; Bozdag‐Turan et al, ). Thus, exogenous stimulation of blood vessel formation by cell transplantation is under intense investigation for the treatment of ischemic disease.…”
Section: Commentarymentioning
confidence: 99%